Voyages of body and soul selected female icons of India and beyond - edited by Katrak, Ketu H. (Cambridge Cambridge Scholars Publishing, 2014)
Voyages of Body and Soul: Selected Female Icons of India and Beyond includes scholarly essays and performance/choreographic notes from a diverse range of contributors on the themes of "Mad and Divine: India's Female Saint-Poets" and "Epic Women of India and Beyond." The contributors explore the tendency of patriarchal societies to label exceptional saint-poets yearning for the divine as "mad" because of their resistance to normative and acceptable female behavior. Scholars and performers journey across history, with discussions ranging from the 8th century Tamil mystic poet Andal's divine poetry, to the 16th century saint-poet Meerabai, to figures across the Indian subcontinent, including Kashmir's Lalleshwari and Maharashtra's Janabai, who, as a low caste member, joined the sacred path partly to escape caste oppression. The definition of "epic women" in this volume is multi-faceted: from looking at commonly accepted epic figures, such as the iconic Sita from The Ramayana, to examining epic women in politics, to probing dark women with passions of epic proportions, to legendary teachers of the classical dance style of bharatanatyam, to women with monumental courage and creativity across historical time-periods and geographical locations-Ancient Greece, Ancient India, 20th century Mexico, and Myanmar. Voyages of Body and Soul recognizes creative and courageous female saint-poets, and outspoken women in ancient epics and in contemporary times who follow their chosen paths with deep devotion. Their lives and works are models for the human community in the 21st century.